Characteristic Changes in First-Visit Patients with Peripheral Facial Palsy before and during COVID-19 Pandemic: Focused on a Korean Medicine Hospital - Yoonji Lee; Suji Lee; Yong-Suk Kim (MEDrang Inc., 2024)
This study aimed to analyze whether the coronavirus disease 2019 (COVID-19) pandemic affected the characteristics of first-visit patients with peripheral facial palsy (PFP) and observe changes in their characteristics. This study analyzed the electronic medical records of 2,310 first-visit patients with PFP who visited the Facial Palsy Center, Kyung Hee University Korean Medicine Hospital from January 1, 2019, to December 31, 2021, in terms of demographic characteristics, disease phase, residence locations, hospital visit route, and patient care. During COVID-19, the proportion of acute patients increased by 5.3%, the proportion of visits by residents in Seoul increased by 3.8%, and the proportion of patients receiving only outpatient treatments increased by 12.8%. Significant relationships were present between the presence of the COVID-19 pandemic and the number of patients by disease phase (p = 0.043), residence locations (p = 0.003), and patient care (p = 0.003). Thus, several differences in the characteristics of first-visit patients with PFP visiting a Korean medicine hospital during the COVID-19 pandemic in terms of demographic characteristics, disease phase, residence locations, and patient care.